The histone demethylase JMJD2B regulates endothelial-to-mesenchymal transition - Glaser, Simone F.; Heumüller, Andreas W.; Tombor, Lukas; Hofmann, Patrick; Muhly-Reinholz, Marion; Fischer, Ariane; Günther, Stefan; Kokot, Karoline E.; Hassel, David; Kumar, Sandeep; Jo, Hanjoong; Boon, Reinier A.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2020)
Endothelial cells play an important role in maintenance of the vascular system and the repair after injury. Under proinflammatory conditions, endothelial cells can acquire a mesenchymal phenotype by a process named endothelial-to-mesenchymal transition (EndMT), which affects the functional properties of endothelial cells. Here, we investigated the epigenetic control of EndMT. We show that the histone demethylase JMJD2B is induced by EndMT-promoting, proinflammatory, and hypoxic conditions. Silencing of JMJD2B reduced TGF-β2-induced expression of mesenchymal genes, prevented the alterations in endothelial morphology and impaired endothelial barrier function. Endothelial-specific deletion of JMJD2B in vivo confirmed a reduction of EndMT after myocardial infarction. EndMT did not affect global H3K9me3 levels but induced a site-specific reduction of repressive H3K9me3 marks at promoters of mesenchymal genes, such as Calponin (CNN1), and genes involved in TGF-β signaling, such as AKT Serine/Threonine Kinase 3 (AKT3) and Sulfatase 1 (SULF1). Silencing of JMJD2B prevented the EndMT-induced reduction of H3K9me3 marks at these promotors and further repressed these EndMT-related genes. Our study reveals that endothelial identity and function is critically controlled by the histone demethylase JMJD2B, which is induced by EndMT-promoting, proinflammatory, and hypoxic conditions, and supports the acquirement of a mesenchymal phenotype.